Electrostatic Fermi level tuning in large-scale self-assembled monolayers of oligo(phenylene–ethynylene) derivatives. Issue 10 (1st August 2022) - Wang, Xintai; Ismael, Ali; Ning, Shanglong; Althobaiti, Hanan; Al-Jobory, Alaa; Girovsky, Jan; Astier, Hippolyte P. A. G.; O'Driscoll, Luke J.; Bryce, Martin R.; Lambert, Colin J.; Ford, Christopher J. B.
Abstract : Understanding and controlling the orbital alignment of molecules placed between electrodes is essential in the design of practically-applicable nanoscale electronic devices. Abstract : Understanding and controlling the orbital alignment of molecules placed between electrodes is essential in the design of practically-applicable molecular and nanoscale electronic devices. The orbital alignment is highly determined by the molecule–electrode interface. Dependence of orbital alignment on the molecular anchor group for single molecular junctions has been intensively studied; however, when scaling-up single molecules to large parallel molecular arrays (like self-assembled monolayers (SAMs)), two challenges need to be addressed: 1. Most desired anchor groups do not form high quality SAMs. 2. It is much harder to tune the frontier molecular orbitals via a gate voltage in SAM junctions than in single molecular junctions. In this work, we studied the effect of the molecule–electrode interface in SAMs with a micro-pore device, using a recently developed tetrapodal anchor to overcome challenge 1, and the combination of a single layered graphene top electrode with an ionic liquid gate to solve challenge 2. The zero-bias orbital alignment of different molecules was signalled by a shift in conductance minimum vs. gate voltage for molecules with different anchoring groups. Molecules with the same backbone, but a different molecule–electrode interface, were shown experimentally to have conductances that differ by a factor of 5 near zero bias. Theoretical calculations using density functional theory support the trends observed in the experimental data. This work sheds light on how to control electron transport within the HOMO–LUMO energy gap in molecular junctions and will be applicable in scaling up molecular electronic systems for future device applications.